Pregnancy after urinary diversion at young ages: risks and outcome - Younsi, Nina; Honeck, Patrick; Neisius, Andreas; Thüroff, Joachim W.; Stein, Raimund (Urology, 2017)
Objective: To assess the urologic and obstetric outcomes during and after pregnancy following urinary diversion (UD) performed during childhood or adolescence. Materials and Methods: From our UD database, we identified 25 women who became pregnant between 1981 and 2013. Reasons for UD were neurogenic bladder, exstrophy, trauma, sinus urogenitalis, and interstitial cystitis. Seventeen had continent cutaneous diversion, 4 had continent anal diversion, and 4 had colonic conduit. Results: The average age at delivery was 27.8 (18-39) years. Thirty-seven pregnancies occurred; 1 patient decided for an induced abortion. Thirty-two healthy children were born. Five patients had a spontaneous abortion before the 12th week. Main urologic complications were urinary tract infections in 11 of 32 successful pregnancies. Twelve patients presented with dilatation of the upper urinary tract; 3 of them required a temporary nephrostomy tube. Four of 25 patients required an indwelling catheter because of difficulties of clean intermittent catheterization. One small bowel injury occurred during cesarean section. One patient with exstrophy developed uterine prolapse; 1 nipple prolapse was surgically repaired in the same anesthesia after the cesarean section. Two patients had 3 vaginal deliveries, whereas 28 had a cesarean section. All children were healthy, without malformation, and with mean Apgar scores of 7.8, 8.9, and 9.7 for the 1st, 5th, and 10th minutes of life, respectively. No persistent urologic complications were observed. Conclusion: After UD, pregnancy is possible without major complications. Because of an increased risk of pyelonephritis and dilatation of the upper urinary tract requiring intervention, these pregnancies should be considered high-risk pregnancies. Delivery should be carried out in a center of expertise with urologic standby.
Gesehen am 13.09.2018